Pertanggungjawaban Pidana Terhadap Residivis Tindak Pidana Narkotika (Studi Putusan Nomor 127/Pid.Sus/2025/PN Baubau) - Nawir Dwi Saputra; La Ode Mhammad Karim; Jamil (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Criminal liability against recidivists in narcotics offenses raises a significant legal problem because it involves offenders who have previously served a criminal sentence but repeat the same offense, in this case while still serving a sentence for an earlier narcotics conviction at Class IIA Correctional Institution of Baubau. This study aims to examine criminal liability of narcotics offense recidivists under Indonesian criminal law and to analyze the judge's considerations in imposing a sentence on the recidivist in Decision Number 127/Pid.Sus/2025/PN Baubau. This research employs a normative legal method using statute, case, and conceptual approaches, with primary, secondary, and tertiary legal materials collected through library research and analyzed descriptively-qualitatively. The results show that criminal liability for narcotics recidivists in Indonesia remains grounded in the principle of culpability, so that recidivist status does not automatically render a person criminally liable; the status functions instead as an aggravating circumstance whose application must nevertheless observe the specific arrangement of Article 144 of Law Number 35 of 2009 on Narcotics as lex specialis. In Decision Number 127/Pid.Sus/2025/PN Baubau, the panel of judges proved the elements of the narcotics offense under Article 114 paragraph (2) in conjunction with Article 132 paragraph (1) of the Narcotics Law before considering the defendant's recidivist status, the fact that the offense was committed while serving a previous sentence, the defendant's active role in organizing the narcotics distribution, and the quantity of narcotics involved, while still weighing mitigating circumstances. These considerations resulted in a sentence of twelve years of imprisonment and a fine of Rp1,000,000,000.00, reflecting a sentencing orientation that combines retribution, special and general prevention, and the protection of society.